Republic of Turkey (Washington, D.C.)
1 mikrofiş (4 poz)
Keywords: Supersedes the Agency's National Basic Intelligence Factbook (entry 4). Brief, basic data is given on Turkey's population, political organization, economic conditions, communications, and labor and military forces, plus information on the country's membership in international organizations.